Antleishmanial activity of leaf extract form Calophyllum rivulare against Leishmania amazonensis. - Cuesta Rubio, Osmany (United Arab Emirates, 2014)
Calophyllum rivulare is an endemic tree from Cuba that belongs to Clusiaceae family. This plant had revealed it to be a rich source of pyranochromanone acids including compounds with a variety of biological potentialities such as antioxidant, antiulcer, anticancer and anti-Helicobacter pylori activities. Herein, antileishmanial and cytotoxic activities of extracts obtained from C. rivulare leaves (rich in pyranochromanone acids) and amentoflavone were compared. Extracts were prepared by maceration employing ethyl acetate (CR-1) and methanol (CR-2) as solvents and amentoflavone was isolated from both extracts. The CR-2 extract showed the better activity against the parasite, with an IC50 value of 95.1 ± 5.4 µg/mL and 20.6 ± 1.4 µg/mL against promastigote and amastigote forms, respectively. This extract showed lower cytotoxicity (IC50=182.4 ± 2.3 µg/mL) against peritoneal macrophage from BALB/c mice and a selectivity index of 9. Amentoflavone showed an IC50 of 5.9 ± 0.3 µg/mL against amastigote form and a selectivity index of 9. Results suggest that CR-2 extract and amentoflavone could be explored as new antileishmanial alternatives.
Keywords: Emirates Journal of Food and Agriculture; AMENTOFLAVONA; CALOPHY RIVULARE; LEISHMANIA